John Stuart Mill, Virtues and the Laboring Classes, with Notes on McCloskey - Joseph Persky (Journal of Contextual Economics – Schmollers Jahrbuch, 2020)
Deirdre McCloskey's work on bourgeois virtues is pathbreaking, but it has relatively little to say about working class virtues. The present paper turns to John Stuart Mill (a McCloskey favorite) for his take on the "future of the laboring classes" (Mill [1848] 1965, 758 – 796). If modern capitalism is the world created by McCloskey's bourgeois virtues, what would the world created by Mill's working-class virtues look like? Key to that vision is the emergence of an economy based on producer cooperatives. McCloskey is undoubtedly right that the bourgeoisie has greatly improved the material conditions of the mass of workers, but those workers have been left viewing the larger portion of their lives as instrumental. The major workday virtue of the modern worker remains temperance/discipline. Mill and his wife, Harriet Taylor, anticipate cooperatives as generating a much richer work life, a work life that would encourage the development of a range of virtues in the workers themselves. It is clear that Britain (and most of the rest of the world) has not evolved the way that Mill anticipated. To what extent then must we conclude that a widespread sense of virtue has slipped through our hands?
Keywords: A13; B12; J54; 330; John Stuart Mill; Deirdre McCloskey; Laboring Classes; Virtue; Temperance